Association-based process integration for compliance with core standards in development of medical software - Kim, Dong Yeop; Park, Ye Seul; Lee, Byungjeong; Lee, Jung Won (Lecture Notes in Electrical Engineering, 2018)
Several standards for medical software require systematic development to ensure safety and performance. Core standards for medical software include IEC 60601-1, IEC 62034, and ISO 14971. And they present different activities. In this case, standards consist of contents related to development by referring to contents of one another. Therefore, it is difficult for a developer to identify reference-relationships with other standards for complying with one standard. For this, there are rules and studies that assist in the reference-association, but they do not provide the requirements at a view of developer. Therefore, we propose an integrated process to comply with the core standards. The proposed process is defined by analyzing the relationship between development process and so on. Then it includes the requirements and artifacts at each stage of the integrated process. This enables systematic development of medical software by providing the activities and requirements in terms of developer’s view.
Keywords: Development process; Medical software; Process integration; Reference relationships; Medical software; Process integration; Standard compliance